Threads User Decline Analysis Using the Unfield Theory of Acceptance and Use of Technology method - hafiz, Hafiz Zikra (INOVTEK Polbeng - Seri Informatika, 2024)
Threads is the fastest growing software application in history, its success did not last long. users of this application fell more than 75% within 5 days. the purpose of this study was to determine the factors that cause the decline in Threads users. Measurement of user decline was carried out using the Unfield Theory of Acceptance and Use of Technology (UTAUT) using quantitative methods. Several previous studies that tested factors to encourage the use of a system showed that the UTAUT model was proven to be able to explain the acceptance of a technology. Case study on the Threads community with a required sample size of 97 based on the lemeshow formula. The results of the study showed that the variables of performance expectations, facilitation conditions, social influence, had a positive effect on the decline in interest in use. The results of the research analysis showed that the use of Threads did not encourage deep interaction so that users felt less involved and lost motivation to actively subscribe, reviews or suggestions not to use Threads and the lack of superior features that differentiate Threads from other platforms. Influenced the decline in interest in using Threads.